WRITING LEARNING MODEL BASED ON ÉCRITURE AUTOMATIQUE METHOD IN COURSE AUFSATZ I - M. Kharis (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This study aims to describe the process and the result of implementing Écriture Automatique writing method for Aufsatz I Course. The research specifically describes the finding based on the data gathered from the questionnaires. The study indicates that the Écriture Automatique method encourages students to write, inspire, and help them elaborate their ideas. From the students’ writing activity in two meetings, their scores are between 84.1 and 80.1 in average from maximum grade 100, both of which are categorized ‘good’